2017
DOI: 10.4172/2151-6200.1000255
|View full text |Cite
|
Sign up to set email alerts
|

Running Head: Destructive Leader Behavior in the Norwegian Armed Forces

Abstract: Recent research indicates that destructive leadership might have a detrimental effect on a wide range of outcomes across the organization. However, few studies have focused on the military context. The present study examined the extent to which destructive leader behavior was related to individual work-related attitudes and feelings among military personnel in the Norwegian Armed forces (N=170). Dependent variables were (1) Burnout, (2) Work Engagement, and (3) Organizational Commitment. Hierarchical regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The leaders/supervisors do so by consistently humiliating their subordinates, invading their privacy, reminding them of their past mistakes or failures, giving them silent treatment, breaking promises made to them, and putting them down in public (Tepper, 2000). Nevertheless, in certain scenarios the destructive behaviors might be indispensable, particularly when there prevails an environment of low performing followers (Rohansen & Platek, 2017).…”
Section: Abusive Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaders/supervisors do so by consistently humiliating their subordinates, invading their privacy, reminding them of their past mistakes or failures, giving them silent treatment, breaking promises made to them, and putting them down in public (Tepper, 2000). Nevertheless, in certain scenarios the destructive behaviors might be indispensable, particularly when there prevails an environment of low performing followers (Rohansen & Platek, 2017).…”
Section: Abusive Supervisionmentioning
confidence: 99%
“…Destructive behaviors of leaders have the potential to cause severe damage to the organization and its constituents (employees), by endangering the wellbeing of its internal stakeholders (Rohansen & Platek, 2017). Abusive supervision (AS) has been found to be the most prominent form of destructive leadership and nearly 273 articles have been published by the leading journals on AS in the last five years (Bhattacharjee & Sarkar, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The primary instrument found to measure passive forms of destructive leadership was the Multifactor Leadership Questionnaire (87% of the studies, see Table 1), though different versions of it were applied. Three of the studies used the instrument, Destrudo L, which is specifically designed to measure destructive leadership behaviour in the military context and includes both active and passive forms of destructive leadership (Fors Brandebo et al, 2016;Johansen & Platek, 2017;Larsson, Fors Brandebo, & Nilsson, 2012).…”
Section: Descriptive Findingsmentioning
confidence: 99%
“…Bass and Yammarino (1991) found that subordinate ratings of laissez-faire leadership were negatively related to superior-rated performance and superiorrated early promotion. Nine studies (33%) examined factors related to subordinate well-being and health (Britt, Wright, & Moore, 2012;Chi & Liang, 2013;Cole & Bedeian, 2007;Fors Brandebo et al, 2016;Johansen & Platek, 2017;Luria, 2008;McGurk et al, 2014;Nahum-Shani, Henderson, Lim, & Vinokur, 2014;Sadler, Mengeling, Booth, O´Shea, & Tomer, 2017). The studies indicated that subordinate reports of laissez-faire leadership behaviour were related to emotional exhaustion (Fors Brandebo et al, 2016 ;Cole & Bedeian, 2007) and PTSD caseness (McGurk et al, 2014) as well as reduced subordinate general health (Nahum-Shani et al, 2014).…”
Section: Descriptive Findingsmentioning
confidence: 99%
See 1 more Smart Citation